Pengaruh Live Streaming, Citra Merk Terhadap Online Customers Review Dalam Mengambil Keputusan Pembelian Produk (Skintific) - Kusuma, Sofia Anida; Ahmadi, Mirzam Arqy (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The purpose of this study is to analyze the influence of live streaming and brand image on online customer reviews. To analyze the influence of live streaming and brand image on purchasing decisions. To analyze the influence of online customer reviews on online customer reviews. To analyze the influence of live streaming and brand image on purchasing decisions mediated by online customer reviews. The sampling technique used in this study was purposive sampling while the population used was consumers or users of skintific products in Surakarta and a sample of 100 consumers or users of skintific products in Surakarta. The results of the live streaming study have a positive and significant effect on online customer reviews. The results of the brand image variable have a significant effect on online customer reviews. The results of the live streaming variable have a positive and significant effect on purchasing decisions. The results of the brand image variable have a positive and significant effect on purchasing decisions. The results of the online customer review variable have a positive and significant effect on purchasing decisions. The results of the mediation show that online customer reviews can mediate positively and significantly between live streaming and purchasing decisions as evidenced by the t-statistic value. The results of the mediation show that online customer reviews can mediate positively and significantly between brand image and purchasing decisions.